Investigating the relationship between God and man in the tragedy of Attar and Haft Aurang Jami - Ghezelsofli, Zahra (2021)
Man, God and their relationship with each other is one of the most fundamental topics in mystical literature. Mystical poets, as the possessors of the gentle and sensitive divine spirit, have included the relationship between God and man in the form of grace and pleasantness, which has become one of the deepest phrases of their works. This study has examined the relationship between God and man in a library and in a comparative way in the tragedy of Attar Neyshabouri and Divan Jami. The purpose of this study is to investigate the relationship between God and man based on the basic human principles of help, guidance and love ... which shows that the relationship between God and man is one of the important concerns of these two mystics and they have different ways and factors to achieve It has provided; The most important results obtained from this research are that the works of Attar and Jami are full of the manifestation of the relationship between God and man, and this relationship is sometimes quoted from the language of the poet and sometimes from the language of fictional characters. The recklessness, boldness and intimacy that exist in the poems of these two have given a special depth to their verses that give the reader a feeling of tenderness and the peak of servitude, while the loving relationship of God has been the highest type of relationship.